Undercurrents of echo chambers and flame wars: party political correlates of social media behavior - Koiranen Ilkka; Koivula Aki; Malinen Sanna; Keipi Teo (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
In this study, we examine how political party preference and politically active social media use associate with social media behaviors - namely, conformist, provocative, and protective - in the context of the current political sphere in Finland. In our empirical analysis, we use a nationally representative dataset collected from 3,724 Finnish citizens in 2018. Our research confirms the assumption that there are notable differences in the social media behaviors of the supporters of different political parties. Additionally, our research shows that politically active social media use increases the occurrence for all three aforementioned behaviors. The study's results also confirm that major differences in online behavior exist among the new identity parties' supporters, who rely heavily on post-materialist and neoconservative political values.